(untitled) (Південний архів (історичні науки), 2026)
The purpose of the article is a comprehensive analysis of the forms, methods, and mechanisms of the KGB`s struggle against the Ukrainian Sixties in the first half of the 1960s, with an explanation of the evolution of the intelligence, operational, and preventive activities of the special service and the preparation of the groundwork for further repressive actions. The methodological basis of the article was the principles of objectivity, historicism, comprehensiveness, continuity, as well as a complex of special-historical and general scientific methods. The work used methods of analysis and synthesis, retrospective, problem-chronological, and the method of comparison and comparison of information from various sources. Results and conclusions. In the first half of the 1960s, the KGB developed specific tactics against the sixties, which differed from practices against underground organizations: instead of mass arrests, agent-operational measures, prevention and ideological pressure dominated. Already in the late 1950s, the foundation of systemic control was laid – an extensive agent network, mass “preventive conversations”, recruitment attempts and interrogations testified to the early institutional reaction of the penal authorities to the activation of the cultural movement. In 1963–1964, pressure took on more pronounced forms: along with public ideological campaigns, agent operations were deployed; in particular, the case of the group development “88” was opened. The totality of the recorded measures indicates a transition from fragmentary supervision to systematic preparation of a large-scale repressive action, implemented as early as 1965. The intensification of preventive work in the mid-1960s indicates that the KGB sought not only to control, but also to intercept the semantic leadership among the Sixties. It is significant that even many hours of conversations and coercion to “repent” did not guarantee the cessation of the Sixties` activity, which led to the further radicalization of the actions of the special services. Active “study” of regional cells and an attempt to connect the Sixties with the OUN underground completed the formation of the narrative about the “heirs of the nationalists”, which became the basis for subsequent arrests. In the first half of the 1960s, an institutional, agentic, and propaganda infrastructure was created to combat the sixties, which determined the nature of the repressive policy of the middle and second half of the decade.